Penerapan Perencanaan Pajak Penghasilan Badan sebagai Strategi Penghematan Pembayaran Pajak pada Yayasan Pendidikan - Alawiya Ashara Syakura; Naruli, Akhmad; Rahayu, Puji (JURNAL PAJAK INDONESIA, 2023)
This research focuses on the implementation of the Tax Expense Reduction on Educational Foundations by applying tax facilities in accordance with the Minister of Finance Regulation Number 68/PMK.03/2020. This research uses a quantitative descriptive method by analyzing secondary data from the Al Huda Islamic Education Foundation to compare calculations. The results of the study reveal that the Education Foundation can minimize the tax payable by reusing the surplus by planning the allocation of the use of surplus, submitting a Statement of the use of surplus to the Tax Office and also attaching details of the use of surplus along with a report in the Annual Corporate Tax Return. So that the Education Foundation can reduce tax payments owed and can maximize the procurement of facilities and infrastructure provided by the Education Foundation.